Temerity and Timidity : Lessons from Tanudjaja v. Attorney General (Canada) - Young, Margot (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2020)
As the case of Tanudjaja v. Attorney-General (Canada) recedes into the past, its legacy persists as powerful threat to law’s potential to evolve, retaining a critical edge of progressive relevance. Tanudjaja brought extensive and bold argument charging that government action and government inaction were responsible for the evolution and perpetuation of Canada’s housing failure. The challenge was dismissed ; its substantive arguments and evidence shut out without full hearing by a judiciary spooked by novelty. But, the case stands as judicial confirmation of patterns of dismissal of social justice claims under the Canadian Charter of Rights and Freedoms. The significance of these patterns extends broadly — imperilling other claims on the litigation horizon such as emerging assertions of environmental rights.